Analisis Penyajian dan Pengungkapan Aset Bersejarah (Studi Kasus Pada Museum Negeri Siwalima Provinsi Maluku) - Titirloloby, Jossep; Lenggono, Tirza Oktovianti; Gainau, Paskanova Christi (Politeknik Ganesha Medan, 2024)
This study aims to determine the disclosure and presentation of Heritage Assets according to PSAP 07 of 2010 at the Siwalima Museum, Maluku Province. The type of research used in this study is a case study research with a qualitative approach. The necessary data were obtained through interviews, observation, documentation, as well as secondary data related to this research. The results of the study show that the presentation of heritage assets is not in accordance with PASP No. 07 of 2010. They are not presented in the Notes to the Financial Statements where historical assets are supposed to be included. Instead, heritage assets are listed in the Notes to the Financial Statements in terms of units, without any corresponding values, but they are explained in the Museum Items Inventory Book.